Microbe-mineral interactions within kimberlitic fine residue deposits: impacts on mineral carbonation - Jones, Thomas Ray; Poitras, Jordan; Levett, Alan; da Silva, Guilherme; Gunathunga, Samadhi; Ryan, Benjamin; Vietti, Andrew; Langendam, Andrew; Southam, Gordon (Frontiers in Climate, 2024)
The observation of photosynthetic biofilms growing on the Fine Residue Deposit (FRD) kimberlite produced by the Venetia Diamond Mine, Limpopo, South Africa suggests that processed kimberlite supports bacterial growth. The presence of this biofilm may aid in the acceleration of weathering of this ultra-mafic host material a process that can sequester CO2 via carbon mineralisation. Laboratory and field trial experiments were undertaken to understand the microbe-mineral interactions occurring in these systems, and how these interactions impact geochemical cycling and carbonate precipitation. At laboratory scale it was discovered that using kimberlite as a growth supplement increased biomass production (up to 25-fold) and promoted microbiome diversity, while the inoculation of FRD systems aided in the aggregation, settling, and dewatering of kimberlitic slurries.Field trial studies combining photosynthetic biofilms (cultured in 3 x 1000L bioreactors) with FRD material were initiated to better understand microbially enhanced mineral carbonation across different depths, and under field environmental conditions. Over the 15-month experiment the microbial populations shifted with the kimberlitic environmental pressure, with the control and inoculated systems converging. The natural endogenous biosphere (control) and the inoculum accelerated carbonate precipitation across the entire 40 cm bioreactor depth, producing average 15-month carbonation rates of 0.57 wt.% and 1.17 wt.%, respectively. This corresponds to an annual CO2e mine offset of ~4.48% and ~9.2%, respectively. Millimetre-centimetre scale secondary carbonate that formed in the inoculated bioreactors was determined to be biogenic in nature (i.e., possessing microbial fossils) and took the form of radiating colloform precipitates with the addition of new, mineralised colonies. Surficial conditions resulted in the largest production of secondary carbonate, consistent with a ca. 12% mine site CO2e annual offset after a 15-month incubation period.